A new dynamic method for measuring hydrogen partial pressure in molten aluminum alloy - Sun Qian; Li Dayong; Wang Lihua (China Foundry, 2011)
Hydrogen partial pressure is an important parameter to calculate hydrogen concentration levels in molten aluminum alloy. A new dynamic method for measuring hydrogen partial pressure in molten aluminum alloy is studied. Dynamic and rapid measurement is realized through changing the volume of the vacuum chamber and calculating the pressure difference ΔP between the theoretical and measured pressures in the vacuum chamber. Positive ΔP indicates hydrogen transmits from melt to vacuum chamber and negative ΔP means the reverse. When ΔP is equal to zero, hydrogen transmitted from both sides reached a state of dynamical equilibrium and the pressure in the vacuum chamber is equal to the hydrogen partial pressure in the molten aluminum alloy. Compared with other existing measuring methods, the new method can significantly shorten the testing time and reduce measuring cost.